2004
DOI: 10.1089/152702904322963690
|View full text |Cite
|
Sign up to set email alerts
|

Increased Oxidative Stress Following Acute and Chronic High Altitude Exposure

Abstract: The generation of reactive oxygen species is typically associated with hyperoxia and ischemia reperfusion. Recent evidence has suggested that increased oxidative stress may occur with hypoxia. We hypothesized that oxidative stress would be increased in subjects exposed to high altitude hypoxia. We studied 28 control subjects living in Lima, Peru (sea level), at baseline and following 48 h exposure to high altitude (4300 m). To assess the effects of chronic altitude exposure, we studied 25 adult males resident … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(96 citation statements)
references
References 37 publications
8
79
1
3
Order By: Relevance
“…In contrast, the maximal exercise performed under hypoxia induced a significant increase in plasma MDA ( þ 56%) and AOPP ( þ 44%). Cellular generation of ROS under hypoxia was reported previously in animals at rest (Hitka et al, 2003), and in humans at high altitude (Simon-Schnass, 1996;Jefferson et al, 2004) and in hypobaric chambers (Joanny et al, 2001).…”
Section: Effects Of Maximal Exercise Under Normobaric Hypoxia and Normentioning
confidence: 56%
See 1 more Smart Citation
“…In contrast, the maximal exercise performed under hypoxia induced a significant increase in plasma MDA ( þ 56%) and AOPP ( þ 44%). Cellular generation of ROS under hypoxia was reported previously in animals at rest (Hitka et al, 2003), and in humans at high altitude (Simon-Schnass, 1996;Jefferson et al, 2004) and in hypobaric chambers (Joanny et al, 2001).…”
Section: Effects Of Maximal Exercise Under Normobaric Hypoxia and Normentioning
confidence: 56%
“…In resting conditions, oxidative stress markers have been detected in humans under hypobaric hypoxia (Bailey et al, 2001a;Jefferson et al, 2004), at simulated altitude in hypobaric chambers (Joanny et al, 2001) and after breathing gas mixture reduced in O 2 content (Wing et al, 2003). Firstly, the increase in catecholamine production under hypoxic conditions (Mazzeo et al, 1998) could be responsible for oxidative stress.…”
Section: mentioning
confidence: 99%
“…Permanent residence at high altitude was accompanied by increased oxidative stress (Jefferson et al 2004), and one day of high altitude hypoxia in sedentary lowlanders was associated with increased steady-state levels of oxidative DNA damage (Moller et al 2001). However, prolonged hypoxic exposure in lowlanders showed an adaptive response to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we found that the changes in isoprostanes in plasma and lung lymph were significantly correlated with the severity of hypoxemia 2 hours after oleic acid administrationin the present study. Jefferson et al [23] measured plasma isoprostane concentrations after acute (48 hours) and chronic high altitude exposures in normal subjects and found significantly increased levels of isoprostanes. These findings were consistent with those of another report showing increased levels of plasma thiobarbituric acid reactive substances in normal subjects after exposure to chronic hypoxia [24].…”
Section: Discussionmentioning
confidence: 99%